10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Background Spinal anesthesia-induced hypotension (SAIH) is common in hypertensive patients, yet reliable preoperative markers remain limited. Corrected carotid flow time (CCFT) is a Doppler-derived index influenced by preload and ventricular ejection timing, but its association with SAIH in this population has not been established. Objective To evaluate whether preoperative CCFT is independently associated with SAIH in hypertensive patients undergoing spinal anesthesia. Design Single-center prospective observational study. Setting University hospital, operating room. Patients 110 hypertensive adults scheduled for lower abdominal or lower extremity surgery under spinal anesthesia. Interventions Preoperative carotid and brachial ultrasound assessments (CCFT, carotid intima-media thickness [CIMT], flow-mediated dilation [FMD], carotid blood flow [CBF], and internal jugular vein collapsibility index [IJV-CI]) were performed. Hemodynamics were recorded for 30 minutes after spinal injection. Main outcome measures Primary outcome: SAIH (≥20% decrease in systolic blood pressure or SBP <90 mmHg sustained for ≥1 minute). Secondary outcomes hemodynamic trends and discriminative performance of ultrasound parameters. Results SAIH occurred in 54 patients (49.1%). CCFT was shorter in patients who developed hypotension (326.5±71.3 vs. 437.3±82.9 ms, p<0.001). In the primary multivariable model including CIMT, FMD, and beta-blocker use, CCFT remained independently associated with SAIH (aOR 0.980 per 1-ms increase, 95% CI 0.973-0.988, p<0.001). CCFT alone had an AUC of 0.854 (95% CI 0.785-0.924); the 358.5-ms cut-off had 74.1% sensitivity and 87.5% specificity. A clinical model including age, baseline SBP, and beta-blocker use had an AUC of 0.572 (95% CI 0.465-0.679); adding CCFT increased the AUC to 0.866 (95% CI 0.799-0.932; paired comparison p<0.001). Conclusions Preoperative CCFT was independently associated with SAIH and improved discrimination when added to a parsimonious clinical model. The cohort-derived threshold requires external validation before clinical implementation. Trial registration ClinicalTrials.gov (https://clinicaltrials.gov/), NCT06749184.